Il defectus discretionis iudicii nel sistema matrimoniale canonico. Parte seconda. Caratteristiche e peculiarità della discretio iudicii (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. Discretio iudicii abituale e attuale - 2. Gravità del defectus iudicii - 3. L’influsso del defectus iudicii sugli iura et officia matrimonialia essentialia mutuo tradenda et acceptanda.Discretio iudicii, mental disease, iura et officia matrimonialia essentialia, nullity of marriage, psychic ability to marry.ABSTRACT: The present essay, starting from the legal regulation of the discretio iudicii in the canon law system, tries to specify its conceptual essence and its peculiar characteristics relatively to the matrimonial institution. Particular attention has been paid to the attempt to clarify the connection between the defectus discretionis iudicii and the iura et officia matrimonialia essentialia and also the incidence of the different kinds of mental diseases on the expression of a valid matrimonial consent.